Cogency of Capital Structure Theories to an Islamic Country: Empirical Evidence from the Kuwaiti Banks - Naser, Kamal; Al- Mutairi, Abdullah; Al Kandari, Ahmad; Nuseibeh, Rana (International Journal of Economics and Financial Issues, 2015)
This study is set out to examine the cogency of capital structure theories in a unique Islamic financial environment where tax shield is irrelevant, paying or receiving interest is undesirable and government exercises control over major economic activities. To achieve this objective, the annual reports of all Kuwaiti banks listed on the Kuwait Stock Exchange (KSE) for the period between 2010 and 2014 were used to extract internal bank variables. In addition, external macroeconomic data were extracted from World Bank statistics. The results of the pooled regression analysis disclosed that the capital structure of the Kuwaiti banks are influenced by their size measured by total assets, cash dividends paid and the market value/ book value of the bank's share. While the result was inconsistent with agency theory, it provides support to the pick-order, trade off and market theories. Keywords: Capital structure; firm size; Pecking Order Theory; Static Trade-off Theory; Banking Sector; Kuwait Stock Exchange; Kuwait JEL Classifications: C42; G21; G32